Identities and Foreign Policies in Russia, Ukraine and Belarus - White, Stephen; Feklyunina, Valentina; SpringerLink (Online service) (London : Palgrave Macmillan UK, 2014)
This book maps changing definitions of statehood in Russia, Ukraine and Belarus as a result of their exclusion from an expanding Europe. The authors examine the perceptions of the place of each state in the international political system and its foreign policy choices, and draw comparisons across the region.
Keywords: Political science; Europe -- Politics and government; European Union; Russia -- Politics and government; International relations; Globalization; Political Science and International Relations; International Relations; European Politics; Russian and Post-Soviet Politics; European Union Politics; Political Science; Globalization